PENERAPAN STRATEGI PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 01 BUANTAN LESTARI KECAMATAN BUNGARAYA KABUPATEN SIAK - Saadi Saadi; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to improve learning outcomes IPA IV Elementary School Grade 01 Buantan Lestari many as 31 students. The learning process of teachers has been rarely involves the knowledge and experience of students, more teachers pursue the matter with the target achievement discussions and presentations, so that student learning outcomes have not reached the minimum completeness criteria. Researchers used the design of classroom action research conducted in two cycles. Each cycle is done twice a meeting with one daily tests each end of the cycle. Data were collected through observation sheet teacher, student observation and student learning outcomes by using descriptive analysis. The results showed that the application of learning strategies concept maps significantly affect student learning outcomes. Setrategi amount of influence can be seen from the results of the data completeness and classical individual student learning outcomes, cycle I and II, which showed an increase as expected. This is evidenced in the results of studying pre-study students completed only 8 (25.8%), while the students did not complete as many as 24 (77.4%) with classical completeness is only 25.8%. While in the first cycle of students who completed a total of 18 (58.1%) who did not complete 13 (77.4%), with classical completeness increased to 58.1% with a 32.3% increase. In the second cycle students who pass as many as 25 (80.6%), while the students who did not complete as many as six (19.4%) classical completeness increased again reaching 80.6% with an increase of 54.8%. This means classical completeness criteria have been achieved as a result of classical completeness above 75%. This success is due to the use of learning strategies concept map activity students become more active, which means that students are more likely to be positive in the following learning process provided by the teacher as well as in performing manufacturing operations concept maps.Keywords : Strategy Concept Map, Learning outcomes